Using the signal-to-noise ratio of GPS records to detect motion of structures - Peppa, Ioulia; Psimoulis, Panos; Meng, Xiaolin (Wiley, 2018)
Although major breakthroughs have been achieved during the last decades in the use of Global Positioning System (GPS) technology on structural health monitoring, the mitigation of the biases and errors impeding its positioning accuracy remains a challenge. This paper tests an alternative approach that can increase the reliability of the GPS system in structural monitoring by using the spectral content of the signal-to-noise ratio (SNR) of GPS signals to detect frequencies of antenna vibrations. This approach suggests the potential of using SNR data analysis as a supplement to low-quality positioning solution or as a near real-time alert of excessive vibration proceeding the position solution calculation. Experiments, involving a GPS antenna subjected to vertical vibrations of 0.4- to 4.5-cm amplitude at a range of frequencies between 0.007 and 1 Hz, examine the dynamic multipath-induced SNR response corresponding to the antenna motion. Synchronised fluctuations in the SNR time series were observed to reflect the antenna motion and their spectral content to include the frequencies of motion. SNR records from the GPS monitoring of the Wilford suspension bridge were used to validate the SNR sensitivity to controlled vibrations of the bridge deck. The natural frequency of 1.64 Hz was extracted from SNR measurements using spectral analysis on a 6-mm amplitude vibration, and the frequency of the semistatic displacement (∼0.02 Hz) was revealed in the SNR records permitting, after appropriate filtering, the estimation of a few millimetre semistatic displacement from the GPS time series without the need for any other sensor.